Long‐Lifetime Triboelectric Nanogenerator Operated in Conjunction Modes and Low Crest Factor. Issue 7 (15th January 2020) - Li, Xinyuan; Yin, Xing; Zhao, Zhihao; Zhou, Linglin; Liu, Di; Zhang, Chunlei; Zhang, Chuguo; Zhang, Wei; Li, Shaoxin; Wang, Jie; Wang, Zhong Lin
Abstract: The high‐output triboelectric nanogenerator (TENG) is indispensable for its practical applications toward industrial products. However, the electricity loss in simple parallel connection among all units and the typically high crest factor output seriously hamper the practical applications of TENG. Here, a rectified TENG is reported in parallel structure to solve the problem of electricity loss in simple parallel connection. The rotational contact–separation structure with phase difference between rectified TENGs addresses high crest factor output and extends service life of rotational TENG simultaneously. The current crest factor is dramatically decreased to 1.31 in multiple rectifier multiple TENG in parallel (MRM‐TENG), while that of TENG in simple parallel is higher than 6. Meanwhile, the current output can retain up to ≈93% of its initial performance after 7 200 000 rotations under 2.00 r s −1 of 1000 h. Furthermore, the equivalent current can be in linear growth with low crest factor by making MRM‐TENG in parallel for distributed energy supply without electricity loss. This work may provide a new strategy for TENG in parallel to achieve a low crest factor output and long‐term cycling stability power generation in distributed energy harvesting for large‐scale power application. Abstract : A universal method to reduce the crest factor of triboelectric nanogenerators is theoretically proposed, and a long‐lifetime triboelectric nanogenerator with low crest factor is achieved by using the rotational contact–separation structure with phase difference.